Albumin polymorphism and its association with economic traits in Hariana and its exotic halfbreds - SENAPATI, P K; DATTAGUPTA, R; CHATTERJEE, A K; SINHA, R (The Indian Journal of Animal Sciences, 2013)
Serum albumin polymorphism was studied, respectively, in 65,67,74 Holstein x Hariana (HL x H), Brown Swiss x Hariana (BS x H) and Jersey x Hariana (Jr x H) halfbreds, and 69 pure Hariana (H) cows maintained at Government farms of Haringhata. West Bengal. It revealed only 2 albumin codominant alleles - A1bA and A1bB, the former being faster in mobility. The frequency of A1bA and A1bB ,the former beging faster in mobility. The freauenee A1 was higher (around 0.65) in all the crossbreds and lower (0.18) in indigenous cows. The phenovariants A1bAA AlbBB and A1bAB were present in all the genetic groups with the only exception of HL x H which lacked in A1b BB The BS x H and H out of the 4 studied population were in equilibrium.